Amina Wadud’s Criticism against Misogynistic Interpretation of Quran: a Study of Hermeneutic Feminism . - NFN Mardety (Jurnal Perempuan, 2015)
This paper is an analysis of Amina Wadud’s thinking about Islam and the status of women, especially regarding gender bias in the interpretation of the Alquran. Methodological problems in the interpretation of the Alquran has led gender issues that disadvantage women. Gender issues in the interpretation has made women subordinate, scapegoated, subordinated and oppressed. Thus, in order to achieve gender equality, Wadud dismantles gender bias in the interpretation of the Qur’an and reveal the darkness of the status of women. Furthermore, Wadud first interpretation offered by women, an interpretation which echoes the voice of women in the Qur’an.